Exploring the feasibility of a mental health application (JoyPopTM) for Indigenous youth - Au-Yeung, Allison; Marfatia, Daksha; Beers, Kamryn; General, Daogyehneh Amanda; McQueen, Kahontiyoha Cynthia Denise; Martin-Hill, Dawn; Wekerle, Christine; Green, Tehota'kerá:ton Jeremy; , The Six Nations Youth Mental Wellness Committee; Bomberry, Tristan; Hill, Lori Davis; General, Daogyehneh Amanda; et al. (Frontiers in Psychiatry, 2023)
Objective: The purpose of the current study is to explore the acceptability and feasibility of a resilience-focused mobile application, JoyPop™, for use with Indigenous youth. Methods: A Haudenosaunee community-based research advisory committee co-developed the research project, in accordance with OCAP™ principles. Adopting a mixed-method approach, five youth from an immersion school used the JoyPop™ app for four consecutive weeks, as well as completed pre-test questions and weekly usage surveys. Most participants also completed post-test questions and a semi-structured interview. Based on a semi-structured interview protocol, youth responded to questions and the most common themes were categorized to capture the experience of using the app. Results: All youth reported a positive impression, used the app daily, found it easy to navigate, and indicated that they would recommend it to a friend. All features were uniformly positively endorsed. There were features which youth used most often (Deep Breathing, “SquareMoves” game, and Art features) and moderately (Rate My Mood, Journaling, SleepEase). The social connection feature, Circle of Trust, was least utilized, with youth reporting a preference for in-person problem-solving. The dropdown menu of crisis helplines was not used. Youth recommended more gaming options. In terms of cultural resonance, appreciation for the app using water sounds in the SleepEase feature was expressed, as well as cultural consistency with the “Good Mind” perspective. Recommendations included additional nature sounds, Indigenous design elements, inclusion of Native language words, and traditional stories. Discussion: The JoyPop™ app was positively received by Six Nations youth and ways to ensure its cultural appropriateness were identified. Moving forward, it is recommended that Indigenous designers create a new version with community design co-creation. Additional research with various groups of Indigenous youth is warranted, as a pan-Indigenous approach is not recommended.